EXPLORING THE DESIGN OF PERFORMANCE DASHBOARDS IN RELATION TO ACHIEVING ORGANISATIONAL STRATEGIC GOALS - Bugwandeen, Keshika; Ungerer, Marius (The South African Journal of Industrial Engineering, 2019)
Inadequate information sharing and ineffective monitoring are obstacles to strategy execution in an organisation. Performance dashboards are an information system tool used to translate theorganisation’s strategy into objectives, metrics, initiatives, and tasks for each group and individual in the organisation; however, many organisations have been unable to implement dashboards successfully. The primary objective of the research was to explore the design of performance dashboards in relation to achieving strategic goals. The literature revealed mandatory criteria for dashboard design. Dashboards are a business enablement tool, and their success rests on a structured development process with adequate stakeholder involvement.